Dynamics of evoked responses in hippocampal pathways are encoded by the duration of vigilance states - Paul Marchal; Paul A. Salin; Mégane Missaire; Manon Rampon; Julien Carponcy; Régis Parmentier; Gina Poe; Gaël Malleret; Jean-Christophe Comte (Nature Communications)
Abstract Interactions among brain areas are essential to most cognitive functions. Neuronal interactions between these areas depend on the modulation of synaptic strength. However, this modulation remains poorly understood. We recorded evoked responses at four hippocampal pathways in freely moving male rats across 24 hours. We show that synaptic strength at these pathways oscillates with a very slow periodicity and correlates with the durations of vigilance states. A model based on hypnogram data and synaptic strength at one pathway was able to predict the evolution of synaptic strength at most pathways, except one. These results reveal that the temporal succession of vigilance states may contribute to memory processes through rapid modulation of synaptic strength at several pathways during the sleep-wakefulness cycle, suggesting that memory processes are not only dependent on sleep amount but also on sleep architecture.